2018
DOI: 10.3390/ma11050848
|View full text |Cite
|
Sign up to set email alerts
|

Energy Storage Analysis of a Mixed R161/MOF-5 Nanoparticle Nanofluid Based on Molecular Simulations

Abstract: The thermal properties of refrigerants can be modified by adding porous nanoparticles into them. Here, molecular simulations, including molecular dynamics and grand canonical Monte Carlo, were employed to study the thermal energy storage properties of an R161/MOF-5 nanofluid. The results show that the thermodynamic energy change of MOF-5 nanoparticles is linear to the temperature. The adsorption heat calculated by grand canonical Monte Carlo is close to that calculated by the Clausius–Clapeyron equation. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…The specific heat capacity of UIO-66 is Cp = 2 21 (kJ/kg K) by corresponding calculation. This is different from the data reported [26,31,32] in the literature, mainly due to the different structures and components of MOFs. According to formula (1), the specific enthalpy difference Δh UIO-66 and desorption heat Δh desorption of UIO-66 in mixed working medium R1234ze/UIO-66 are calculated.…”
Section: Msd Simulated Fluid Diffusion Detailscontrasting
confidence: 99%
“…The specific heat capacity of UIO-66 is Cp = 2 21 (kJ/kg K) by corresponding calculation. This is different from the data reported [26,31,32] in the literature, mainly due to the different structures and components of MOFs. According to formula (1), the specific enthalpy difference Δh UIO-66 and desorption heat Δh desorption of UIO-66 in mixed working medium R1234ze/UIO-66 are calculated.…”
Section: Msd Simulated Fluid Diffusion Detailscontrasting
confidence: 99%
“…The results showed that MOFs could store more CO 2 while consuming less energy compared to traditional storage systems. Wang et al (2018) studied the adsorption and energy storage of R161 and similar refrigerants in MOF-5. It was found that fluorine atoms in the organic working pairs enhanced their adsorption in MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs, as the emerging porous crystalline materials, are formed from coordinating metal ions and organic ligands. 11 MOFs' unique characteristics, such as excellent porosity, large surface areas, diverse structures/functions, and unsaturated metal sites, lead to their widespread applications in the fields of gas absorption, 12 energy storage, 13 electrochemiluminescence, 14 etc. Moreover, the inherent coordination between metals or metal clusters and organic linkers in MOFs provides great flexibility in modulating their semiconductor properties to enhance the sensitivity of light collection and light response.…”
Section: Introductionmentioning
confidence: 99%